Immobilization of silver nanoparticles on exfoliated mica nanosheets to form highly conductive nanohybrid films. (26th October 2015) - Chiu, Chih-Wei; Ou, Gang-Bo; Tsai, Yu-Hsuan; Lin, Jiang-Jen
Abstract: Highly electrically conductive films were prepared by coating organic/inorganic nanohybrid solutions with a polymeric dispersant and exfoliated mica nanosheets (Mica) on which silver nanoparticles (AgNPs) had been dispersed in various components. Transmission electronic microscopy showed that the synthesized AgNPs had a narrow size distribution and a diameter of approximately 20 nm. Furthermore, a 60 μ m thick film with a sheet resistance as low as 4.5 × 10 −2 Ω/sq could be prepared by controlling the heating temperature and by using AgNPs/POE-imide/Mica in a weight ratio of 20:20:1. During the heating process, the surface color of the hybrid film changed from dark golden to white, suggesting the accumulation of the AgNPs through surface migration and their melting to form an interconnected network. These nanohybrid films have potential for use in various electrically conductive devices.